Using Bloom’s taxonomy to teach course content and improve social media literacy - Callens, Melissa Vosen (Journal of Interdisciplinary Studies in Education, 2019)
Social media can engage students in active learning opportunities and be used toteach almost any course concept. In addition to teaching course concepts, usingsocial media in a classroom can help students critically think about a technologythey use multiple times a day. While some instructors may shy away from usingthese tools, intimidated by the digital natives registered for their courses, theyshould not. Even though most students use social media regularly, many do notknow how to use it professionally. This article will outline activities thatincorporate social media and can be used in any classroom. The activitiescorrespond with each level of Bloom’s revised taxonomy of the cognitivedomain; using this taxonomy allows instructors to introduce social media slowlyand push students toward higher-level thinking.